An Educational CT Scanner Prototype of a 3rd Generation CT Scanner - Sim Ting Lim; Yit Hein Yow; Way Soong Lim; Chee Siong Lim; Li Wah Thong (International Journal of Integrated Engineering, 2025)
This project aims to develop an affordable educational prototype of a 3rd generation CT scanner. The proposed prototype uses non-radiative light sources and combines 3D printing, electronics components, and filtered backprojection (FBP) algorithm to generate the cross-section image of a transparent phantom. Key components include an LED light, an Arduino Nano controller, and a camera. The prototype can capture up to 200 images per scan cycle and successfully reconstruct the internal structures of the phantom. However, there were some limitations, including issues with the dataset, light source power, and time efficiency. Results showed that the prototype could create a 3D model of the lemon phantom, though it faced challenges due to the light source and data limitations. Educational workshops were conducted with 38 students and the prototype was well received by the students as shown by the questionnaire results. Future improvements will focus on increasing dataset resolution, using more powerful light sources like laser diodes, and upgrading the camera system for better image quality and faster processing.